Research Hotspots and Trends on Acupuncture for Anti-Inflammation: A Bibliometric Analysis from 2011 to 2021 - Chen B; Liu D; Li T; Zheng L; Lan L; Yang N; Huang Y (Journal of Pain Research, 2023)
Bing Chen,1,* Di Liu,2,* Tao Li,1 Lijiang Zheng,1 Ling Lan,1 Niu Yang,1 Yinlan Huang1,3 1Ningxia Medical University, Yinchuan, People’s Republic of China; 2Traditional Chinese Medicine Orthopedics and Traumatology Department, General Hospital of Ningxia Medical University, Yinchuan, People’s Republic of China; 3Key Laboratory of Ningxia Ethnomedicine Modernization, Ministry of Education, Ningxia Medical University, Yinchuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yinlan Huang, Ningxia Medical University, No. 1160, Shengli Street, Xingqing District, Yinchuan, People’s Republic of China, Tel +86 18209506917, Email lzdbe@163.comPurpose: We here explored the research status, research hotspots, and development trend of acupuncture against inflammation from both quantitative and qualitative aspects through bibliometrics.Methods: We used CiteSpace and VOSviewer to analyze the literature about acupuncture against inflammation from 2011 to 2021 in the Web of Science Core Collection database by using a visual knowledge map.Results: In total, 1479 articles were included, and the number of articles published each year exhibited an upward trend. The largest number of articles were published in China (661), followed by the United States (287) and South Korea (164). The most productive institution is Beijing University of Chinese Medicine (72), while the most influential institution is the Capital Medical University (0.28). Evidence-based Complementary and Alternative Medicine (131) is the journal that published most articles on the topic. Lin Yiwen is the most prolific author, and Borovikova L is the most influential co-cited author. The keywords that have burst in the last 2 years are inflammation and activation. The keywords with the highest frequency of use are electroacupuncture (EA), inflammation, and expression.Conclusion: The number of publications on acupuncture for anti-inflammation research is rapidly increasing. China is a productive country, but the influence of centrality is poor. Research institutions are concentrated in universities, and the whole collaborative network needs to be strengthened. The anti-inflammatory mechanism of acupuncture is the main focus of research in this field. Regulation of immune cell balance by acupuncture may be a hot topic in mechanism research. At present, immune cells, vagus nerve, signal pathway, inflammatory corpuscles, cytokines and neurotransmitters are popular research topics. In the future, the basic research of acupuncture for anti-inflammation transformed into clinical practice may be a trend. EA and bee venom acupuncture may be promising research directions for acupuncture treatment for inflammatory diseases.Keywords: acupuncture, anti-inflammation, bibliometric analysis, CiteSpace, VOSviewer